Moral competence of dental students: an explanatory mixed-methods study - Raheleh Mosavi; Fatemeh Foroughipour; Maryam Kazemipoor; Fatemeh Keshmiri (BMC Medical Education)
Abstract Aim The present study aimed to investigate the level of four components of moral skills, including moral sensitivity, moral reasoning, moral motivation, and moral courage, among dental students and explore the factors affecting their engagement in moral behavior. Method This is an explanatory mixed-method study conducted in two quantitative and qualitative phases. Participants included undergraduate students in clerkship courses in Dentistry schools (n = 180). In the quantitative phase, the moral skills of students were assessed by a 40-question Moral Skill Inventory. The data were summarized using mean, standard deviation, and frequency (percentage), one sample t-test, independent t-test, and one-way analysis of variance (ANOVA). The students’ experiences were explored through semi-structured interviews in the qualitative phase. Data were analyzed using a conventional content analysis approach, which Graneheim and Lundman introduced. Results The mean score of students was reported 43.61 (6.25). The highest scores were reported in the domain of moral reasoning, and the lowest scores were reported in the domain of moral motivation. The participants’ experiences were explained in the theme “morality as a neglected element in dentistry.” This theme includes two categories: “Disregarding professionalism as a professional responsibility” and “unsupportive behaviors of clinical teachers in a moral dilemma.” Conclusion The results showed a gap between the current and desirable status of dental students' moral skills. Both individual challenges (e.g., prioritizing personal interests) and systemic issues (e.g., lack of constructive feedback and negative role modeling by clinical teachers) were identified as significant barriers to moral behavior. Therefore, the development of students' moral skills requires planning for personal and system factors.